2022
DOI: 10.1261/rna.078972.121
|View full text |Cite
|
Sign up to set email alerts
|

Correlated sequence signatures are present within the genomic 5′UTR RNA and NSP1 protein in coronaviruses

Abstract: The 5’UTR part of coronavirus genomes plays key roles in the viral replication cycle and the translation of the viral mRNAs. The first 75-80 nucleotides, also called the leader sequence, are identical for the genomic mRNA and for the subgenomic mRNAs. Recently, it was shown that cooperative actions of a 5’UTR segment and the non-structural protein NSP1 are essential for both the inhibition of host mRNAs and for specific translation of viral mRNAs. Here, sequence analyses of both the 5’UTR RNA segment and the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 41 publications
4
19
0
Order By: Relevance
“…2D). Swapping experiments of key residues in both NSP1 and SL1 from SARS‐CoV‐1 and ‐2 have demonstrated that these two elements have actually co‐evolved thereby confirming the tight functional link between the NSP1 protein and SL1 hairpin [34]. In these structures of NSP1, the sole N‐terminal domain is visible because the remaining parts of NSP1 are intrinsically disordered [52].…”
Section: Translation Of Viral Transcriptsmentioning
confidence: 99%
See 3 more Smart Citations
“…2D). Swapping experiments of key residues in both NSP1 and SL1 from SARS‐CoV‐1 and ‐2 have demonstrated that these two elements have actually co‐evolved thereby confirming the tight functional link between the NSP1 protein and SL1 hairpin [34]. In these structures of NSP1, the sole N‐terminal domain is visible because the remaining parts of NSP1 are intrinsically disordered [52].…”
Section: Translation Of Viral Transcriptsmentioning
confidence: 99%
“…2A ). NSP1 proteins are conserved in alpha‐ and betacoronaviruses, and therefore were being studied prior to the appearance of SARS‐CoV‐2 [ 34 ]. Early studies in SARS‐CoV‐1 have shown that NSP1 is responsible for efficient shut down of host cell translation [ 35 , 36 , 37 ].…”
Section: Translation Of Viral Transcriptsmentioning
confidence: 99%
See 2 more Smart Citations
“…of all the viral mRNAs and contains five stem-loop structures (SL1 to SL5) that have recently been modelized by chemical probing analyses ( Figure 2 ) [ 73 , 74 ]. These SL are critical for replication, RNA synthesis and escape from nsp1-mediated translation inhibition [ 75 , 76 , 77 , 78 , 79 , 80 , 81 ]; however, they could potentially represent hurdles for translation, notably at the level of ribosome recruitment and scanning. Although the viral genome of SARS-CoV-2 is capped and polyadenylated, the translation initiation mechanism used to locate the AUG start codon inside the SL5 remains undetermined.…”
Section: Introductionmentioning
confidence: 99%